Begonia ’Crested‘: A new variety of Begonia from interspecific hybridization of Begonia sudjanae C.A Janson × Begonia puspitae Ardi - Hartutiningsih-M Siregar; Sri Wahyuni; Mustaid Siregar; Sutomo Sutomo; I Nyoman Lugrayasa; I Made Ardaka (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
Improvement of leaf shape characters in Begonia can be done through hybridization between two different species of Begonia. This study aims to produce a new variety of Begonia to better improve the quantitative, qualitative characters and increase its genetic diversity. The study was conducted in the green house of Bogor Botanic Gardens. Two native species of Indonesia, Begonia sudjanae C.A Janson as the female parent and Begonia puspitae Ardi as the male parent. The mature F1 seeds were sown and selections were made among the plants produced. Observation results the characteristics of the new variety Begonia ‘Crested’ as follows: stem type rhizomatous, leaves simple, ovate, peltate with strongly undulate base. Leaves margin is crenate and apex is acuminate. Colour on the upper surface are yellow green group RHS Colour Chart: (YG 144 A) strong yellow green, colour of veins on upper side is (YG 144 D) light yellow green. Inflorescence peduncle with 20 cm long branched symmetrically. The name Begonia ‘Crested’ as the selected F1 plants are propagated in a vegetative method with leaves cutting, registered on the Center of Plant Variety Protection (PPVTPP) by No. 846/PVHP/2020. This new variety is beautiful and exotic leaves ornamental Begonia which will be developed as commercials ornamental plants.